Analysis of Stages and Princples of Frequency Regulation in Energy Systems - Rafiyev, Sakhavat (ADA University, 2024)
Nowadays, because of the increasing demand for electrical energy, the stability of electrical systems is reaching its critical limit. As the use of renewable energy sources increases in total production, maintaining a stable frequency becomes more challenging. This study discusses frequency regulation by traditional and modern methods and the encountered problems. First-, second, and third-order frequency control systems play crucial roles in maintaining frequency stability. However, with the grow in both the cases and output of renewable sources, it's crucial to seek more advanced solutions, such as synthetic inertia, fast-frequency response technologies, artificial neural networks. This review emphasizes the need for developing algorithms and control strategies that meet the dynamic requirements of modern systems while ensuring reliability and stability. The increase in renewable energy sources in our country and the high rate of trust in them creates several problems in energy systems, one of which is the problems it creates in frequency regulation. Considering that the average electricity production capacity in Azerbaijan is approximately 4500 MW, even if 480 MW of renewable energy is added to this system, many studies and regulations are needed. Although the construction of solar and wind power plants is very useful in itself, it has brought with it many negative effects that undermine the reliability of the energy system, the most significant of which is the inertia of the system and the dependence of energy on natural factors. Traditional frequency regulation systems are a main but increasingly not effective for new power systems. Primary frequency control system manages immediate energy changings by using of generator inertia, when secondary control, often achieved through Automatic Generation Control (AGC), restores the system frequency to nominal. Tertiary control, aiming on resource optimization and economic dispatch, provides a long-term balance. However, the variability and unpredictability of renewable energy require modern solutions that complement these traditional techniques. Advanced frequency regulation approaches, containing synthetic inertia, fast-frequency response (FFR) technologies, and adaptive systems, are very critical in controlling and stabilazing the challenges posed by renewable energy. Synthetic inertia emulates the stabilizing impact of mechanical inertia through power electronics, ensuring rapid responses to deviations. FFR technologies such as battery storage systems (BESS) and flywheel energy storage systems (FESS) provide instantaneous power controls to keep the grid under nominal parameters before slower-acting controls intervene. Furthermore, adaptive control systems like Artificial Neural Networks (ANNs) and Adaptive Neuro-Fuzzy Inference Systems (ANFIS) influence real-time and historical data to optimize responses dynamically, enhancing overall grid resilience. The main objective of this master thesis is to investigate the effects of 3 renewable energy sources that will enter the Azerbaijan's energy system in 2025 on the stability of the system and to pay attention to maintaining the main frequency. The aim of the simulations is to see how, in parallel with the increase in the number of renewable energy sources, when any of the main frequency regulating generators of the system is shutdown, it is felt in other stations and how it is felt on the main Derbent Power Transmission line. Based on the simulation results, new proposals have been put forward, the most important of which is the installation of a new battery system and maintaining stability in the system during emergency shutdowns by remaining in standby mode. Another proposal is the reconfiguration of the AGC and PSS systems at the main Power Plants
Keywords: Electric power systems -- Frequency control; Renewable energy sources -- Integration; Smart grids; Inertia (Mechanics) -- Electric power systems; Energy policy -- Azerbaijan; IT and Engineering